Impacts of climate change on wind erosion in Southern Africa between 1991 and 2015. (9th March 2021) - Zhao, Chaonan; Zhang, Hanbing; Wang, Man; Jiang, Hong; Peng, Jian; Wang, Yanglin
Abstract: Wind erosion is the main form of soil erosion in arid and semiarid areas. It leads to soil loss and land degradation, which aggravates ecosystem vulnerability and threatens regional sustainable development. Exploring wind erosion and associating driving factors can provide useful information to reduce soil wind erosion and solve corresponding environmental problems. Southern Africa is characterized with severe soil wind erosion, which has brought a series of socioeconomic issues, such as food crises and poverty. This study used meteorological and remote sensing data, and the revised wind erosion equation (RWEQ) model to explore the spatio‐temporal dynamics of soil erosion in Southern Africa from 1991 to 2015. The impact of climate change on soil wind erosion was also analyzed. The results showed that wind erosion fluctuated during the study period, which first showed a downward trend and then stabilized at a relatively low level after 2010. Soil wind erosion across 66.65% of the study area significantly decreased ( p  < .05) and near‐surface wind speed was the most important influencing factor. The decrease of wind speed can significantly reduce the soil wind erosion across 39.89% of the study area. Temperature and precipitation were significantly related to soil wind erosion over 18.96% and 24.63% of the study area, respectively. Both can indirectly affect soil wind erosion through their impacts on vegetation cover. This study will help decision‐makers to identify high‐risk areas for soil erosion in Southern Africa and to take countermeasures effectively.